Peningkatan Penguasaan Kanji N3 dengan Model Pembelajaran Berbasis Project Based Learning pada Mahasiswa Pendidikan Bahasa Jepang - Nabilla Khoirunissa Nur Fajriah; Rina Sukmara (Universitas Muhammadiyah Prof. Dr. Hamka, 2022)
This research aims to determine the effectiveness of the project based learning (PJBL) learning model on the Mastery of Kanji N3 for Semester 4 Students of the Japanese Language Education Study Program. This study uses the One Group Pretest Posttest Design research design using the Quasi Experimental method. The population used is the fourth semester students as many as 29 people. This study uses a sampling technique, namely Simple Random Sampling. Based on the calculation, the average value of the pretest is 64.59, the highest score is 89.00 and the lowest is 54.00. for the posttest average value is 73.69, the highest score is 88.00 and the lowest is 54.00. The result of the Mann Whitney test is count 0.001, with a significance level of 0.05, then 0.001 < 0.05, which means that the project based learning (PJBL) learning model is effective in increasing the mastery of kanji. Based on the results of the questionnaire, using the project based learning (PJBL) learning model, students became enthusiastic and active in kanji learning activities, but the project based learning model was still not suitable to be applied to N3 kanji courses.